Lipin1 is required for skeletal muscle development by regulating MEF2c and MyoD expression. (26th December 2018) - Jama, Abdulrahman; Huang, Dengtong; Alshudukhi, Abdullah A.; Chrast, Roman; Ren, Hongmei
Abstract : Key points: Lipin1 is critical for skeletal muscle development. Lipin1 regulates MyoD and myocyte‐specific enhancer factor 2C (MEF2c) expression via the protein kinase C (PKC)/histone deacetylase 5‐mediated pathway. Inhibition of PKCμ activity suppresses myoblast differentiation by inhibiting MyoD and MEF2c expression. Abstract: Our previous characterization of global lipin1‐deficient ( fld ) mice demonstrated that lipin1 played a novel role in skeletal muscle (SM) regeneration. The present study using cell type‐specific Myf5‐cre;Lipin1 fl/fl conditional knockout mice (Lipin1 Myf5cKO ) shows that lipin1 is a major determinant of SM development. Lipin1 deficiency induced reduced muscle mass and myopathy. Our results from lipin1‐deficient myoblasts suggested that lipin1 regulates myoblast differentiation via the protein kinase Cμ (PKCμ)/histone deacetylase 5 (HDAC5)/myocyte‐specific enhancer factor 2C (MEF2c):MyoD‐mediated pathway. Lipin1 deficiency leads to the suppression of PKC isoform activities, as well as inhibition of the downstream target of PKCμ, class II deacetylase HDAC5 nuclear export, and, consequently, inhibition of MEF2c and MyoD expression in the SM of lipin1 Myf5cKO mice. Restoration of diacylglycerol‐mediated signalling in lipin1 deficient myoblasts by phorbol 12‐myristate 13‐acetate transiently activated PKC and HDAC5, and upregulated MEF2c expression. Our findings provide insights into the signalling circuitry that regulates SM development, and have important implications for developing intervention aimed at treating muscular dystrophy. Key points: Lipin1 is critical for skeletal muscle development. Lipin1 regulates MyoD and myocyte‐specific enhancer factor 2C (MEF2c) expression via the protein kinase C (PKC)/histone deacetylase 5‐mediated pathway. Inhibition of PKCμ activity suppresses myoblast differentiation by inhibiting MyoD and MEF2c expression.